A rare presentation of a sacral mass: Ganglioneuroma - Mark A. Colantonio, MD; Matthew Smolkin, MD; Joshua Wiley, DO (Radiology Case Reports, 2025)
Ganglioneuromas are a rare, benign mass, with fewer than 20 cases reported to date with an estimated incidence of 1/40,000. These masses are less frequently found in the sacral region. Although typically benign, these masses can present with discomfort, including abdominal pain, back and pelvic pain, and in some instances, may progress to malignant transformation. Here, we present a rare presentation of a sacral ganglioneuroma in a young female presenting with abdominal pain. We aim to emphasize the importance of multimodal imaging, as well as highlight imaging findings of this rare sacral mass.